2005
DOI: 10.1144/gsl.sp.2005.247.01.17
|View full text |Cite
|
Sign up to set email alerts
|

Hominins and the Early-Middle Pleistocene transition: evolution, culture and climate in Africa and Europe

Abstract: Some of the more important evidence is reviewed for the archaeology of hominin colonization associated with the Early-Middle Pleistocene transition. This is done by reference to the nature of migration 'out of Africa' before the interval of transition, across the transition itself, and then after it. Technologically assisted behaviour may not have been so important in the colonization process, behaviour and biology being the primary factors that led to the success of a migrating species. While climate change a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 70 publications
0
17
0
2
Order By: Relevance
“…Handaxe symmetry has also been argued to have implications for studying the evolution of human cognition (Wynn, 2002). Many authors, however, have suggested that the symmetrical form of Acheulean bifaces may be causally linked to their function as cutting and chopping tools, especially in relation to the task of animal butchery (Jones, 1980;Machin et al, 2007;McBrearty, 2003;McNabb, 2005;Mitchell, 1996;Shea, 2007), and thus that handaxe symmetry was potentially subject to selective forces for adaptive reasons (Simão, 2002). It has also been suggested that handaxe form was a product of sexual selection, whereby artefact symmetry was an indicator of mate fitness (Kohn and Mithen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Handaxe symmetry has also been argued to have implications for studying the evolution of human cognition (Wynn, 2002). Many authors, however, have suggested that the symmetrical form of Acheulean bifaces may be causally linked to their function as cutting and chopping tools, especially in relation to the task of animal butchery (Jones, 1980;Machin et al, 2007;McBrearty, 2003;McNabb, 2005;Mitchell, 1996;Shea, 2007), and thus that handaxe symmetry was potentially subject to selective forces for adaptive reasons (Simão, 2002). It has also been suggested that handaxe form was a product of sexual selection, whereby artefact symmetry was an indicator of mate fitness (Kohn and Mithen, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Most attention paid to the impact of climate events on human migratory patterns has centered on geological-anthropological registers, e.g. Pleistocene outmigration from Africa; see McNabb (2005), 3 and post-glaciation out-migration; see Allen et al (1999). Less attention has been placed, however, on analyzing the impact of climate and weather events on recent human migratory flows.…”
Section: Introductionmentioning
confidence: 99%
“…He emphasizes the contribution of human activities through habitat fragmentation on interference with plant migration to adapt to global climatic change. 3 Based on an archaeological study of hominin colonization associated with the Early-Middle Pleistocene transition,McNabb (2005) points out that climate change and especially shifts in local aridity are explanatory factors of migratory moves out of Africa. However, he concludes, the Achealean behavioral repertoire did not change much across Africa and Europe over a million years, but merely adapted to local conditions.…”
mentioning
confidence: 99%
“…UNESCO does not distinguish between forests and woodlands in terms of woody plant cover, but here, we consider forests to display greater than 80% woody plant cover (7,39). The evolutionary implications of orbital forcing on environmental change were recognized over a century ago (41) but remain controversial today (3)(4)(5)(6) shores document orbital rhythms in terrestrial inputs during the Pleistocene (5), and a growing number of terrestrial sequences hint at a similar pacing for environmental changes in eastern Africa (42,43). Marine sequences are often indirectly or too poorly constrained in time to infer relationships between key junctures in human evolution and terrestrial conditions or change (6).…”
mentioning
confidence: 99%